The effects of particle size distribution and sintering conditions on bending strength of sintered Ni-30%Fe alloys - B. Shongwe, Mxolisi; O. Ajibola, Olawale; M. Ramakokovhu, Munyadziwa; A. Olubambi, Peter (International Journal of Engineering and Technology, 2018)
This work reports effect of the powder grain size distributions on the bending strength sintered Ni-30%Fe alloys obtained from mixed coarse-fine micron size metal powders. Two dissimilar particle sizes of Ni and Fe metal powders were mixed by subjecting them to translational and rotational agitations using the T2F Turbula Shaker Mixer. The mixed powders were moulded using graphite dies and sintered in vacuum and at constant pressure using Spark Plasma Sintering furnace (HHPD-25). The ratios of the two metals were varied as well as the sintering temperature and time. The morphology and microstructures of both powders and sinters were studied using field emission scanning electron microscopy (JSM-7600F) equipped with energy dispersive X-ray spectrometer (EDS) facilities. The phases in the sintered specimens were characterized by X-ray diffraction (XRD). The densities of the samples were determined, The Vickers microhardness at room temperature and bending strength of the sintered alloy specimens were measured. Comparatively, low heating rate (50 oC/min) produced enhanced microstructures hence higher bonding, bending strength and densification than samples at high heating rate (150 oC/min).Â Â